Environmental sensitivity analysis in Turkey - (:unkn) unknown (Inderscience Publishers, 2016)
Enhanced industrialisation without planning and the consideration of the environmental factors brings many problems. Environmental pollution, infrastructure, and urbanisation are among the major issues to be taken into consideration. The Thrace region has started the industrialisation process in 1970s and experienced significant improvements. This research has been conducted by considering the local people's participation in solving the environmental problems, their level of knowledge about the environment, and their discomfort and sensitivity. Factor analysis was applied to digitised data obtained from the judiciary factors, and the resulting factor groups were evaluated in themselves. Surface water pollution region is seen as the most important environmental issue, although most of the businesses located in the Thrace region have waste water treatment plants. It has become mandatory that businesses that use water for industrial purposes should establish and operate a joint treatment plant to improve the life quality of people living in the region. Copyright © 2016 Inderscience Enterprises Ltd.
Keywords: Environmental sensitivity; Factor analysis; Industrial enterprises; Life quality; Turkey